Antenatal care visits and associated factors in Senegal: a multilevel poisson regression analysis of the 2023 DHS survey - Negash, Habtu Kifle; Gebiru, Ashebir Mamay; Getnet, Mihret; Melese, Mihret; Mengistie, Berihun Agegn; Bitew, Desalegn Anmut; Godana, Tilahun Nega; Bizuneh, Yosef Belay; Getahun, Amare Belete; Tilahun, Mikias Mered; Baykemagn, Nebebe Demis; Tassew, Worku Chekol (Frontiers in Global Women's Health, 2025)
BackgroundMaternal health is crucial for women's well-being during pregnancy, childbirth, and postpartum. Antenatal care (ANC) is essential for monitoring health and preventing complications, yet only 35.5% of women in low- and middle-income regions attend the recommended ANC visits. This study explores the socioeconomic and regional factors influencing ANC visits in Senegal.MethodsData from the 2023 Senegal Demographic and Health Survey (DHS) on maternal health were analyzed. A stratified two-stage sampling design selected 400 enumeration areas, and 4,543 women aged 15–49 participated. Independent variables included age, education, wealth, healthcare access, and region. Multilevel Poisson regression in Stata 17 was used to assess factors affecting ANC visits, considering both individual and community-level variables to examine regional disparities and healthcare access.ResultsAmong the 4,543 women, 97.63% attended at least one ANC visit, but only 7.69% completed eight or more. Wealth, media access, education, and regional location significantly influenced ANC attendance. Women from middle-income households attended 6% more visits (AIRR: 1.06, 95% CI: 1.02–1.11), and those from wealthy households attended 8% more (AIRR: 1.08, 95% CI: 1.03–1.14). Women with media access attended 11% more visits (AIRR: 1.11, 95% CI: 1.06–1.15). Regional disparities were evident, with women in Thiès (AIRR: 0.80, 95% CI: 0.73–0.87), Matam (AIRR: 0.83, 95% CI: 0.75–0.92), and Kédougou (AIRR: 0.83, 95% CI: 0.75–0.91) attending fewer visits compared to those in Dakar.ConclusionsThis study identifies significant socioeconomic and regional disparities in ANC utilization in Senegal. Wealth, education, media access, and regional location strongly influence ANC attendance. Targeted policies focusing on maternal health education, healthcare infrastructure, and financial support, particularly in underserved areas, are necessary to improve ANC access and maternal and child health outcomes.